Earth - Lehr James F. (New York : DK Pub., 2004)
A dteail visual overview of Earth's anatomy, tectonics, early life-forms, environment, athmosphere, weather, physical geography, and place in the solar system, which profiles nearly a thousand features on land and in the ocean and contains thousands of color photos and graphics.
Keywords: Earth